PENGARUH JENIS KEMASAN DAN LAMA PENYIMPANAN TERHADAP SIFAT KIMIA, MIKROBIOLOGI DAN ORGANOLEPTIK PERMEN KARAMEL SUSU KAMBING - Susilawati Suslawati; Putri Cyntia Dewi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2011)
Caramel candy is a kind of toffee classified into soft candies, and processed using milk and sugar as the main ingredients. One way to prevent food spoilage is to use suitable packaging as well as storage system. This study was aimed to determine the effects of packaging materials and storage time until 28 days at room temperature and their interaction effects on the the chemical, microbiological, and organoleptic properties , and its accordance with SNI 3457.2 caramel candy standard. The study was conducted in two groups of factors and arranged in Complete Randomized Design with three replications. The first factor was the type of packaging (P) consisted of polyethylene plastic (P1), aluminum foil (P2), and oil paper packaging (P3). The second factor was the duration of storage (L) consisted of 0 days (L1), 7 days (L2), 14 days (L3), 21 days (L4), and 28 days (L5). The homogenity and additivity of the data were tested using Barlett and Tuckey tests, continued using ANOVA , and then further tested using comparison and orthogonal polynomials at of 1% or 5% level of significance. The results showed the samples wrapped in aluminum foil and stored for 28 days at room temperature, was found to be the best type of packaging. The criteria of the best goat’s milk caramel candies were: water content of 5,81% w/w, ash content of 0,95% w/w, reducing sugar content 2,26% w/w, total molds and yeasts 0,49x102 colonies/gram, a total microbial of 2,83 colonies/gram, and the color, texture, taste, and aroma were brown, soft, sweet, and neutral. these criteria met the SNI 3547.2 (2008) quality standard for caramel candies.